Bankruptcy Analysis Using Altman Z-Score Method And Springate Method In Manufacturing Companies In The Footwear Sub-Sector - Rachmawaty, Rachmawaty; Susanto, Susanto (Doktoral Ilmu Manajemen, Universitas Pasundan, 2025)
-